Research progress of spike protein mutation of SARS-CoV-2 mutant strain and antibody development - Huan, Xinkang; Zhan, Jiuyu; Gao, Hongwei (Frontiers in Immunology, 2024)
The coronavirus disease 2019 (COVID-19) is a respiratory disease with a very high infectious rate caused by the Severe Acute Respiratory Syndrome Coronavirus-2(SARS-CoV-2). Because SARS-CoV-2 is easy to mutate, the continuous emergence of SARS-CoV-2 variant strains not only enhances the infectivity of the SARS-CoV-2 but also brings great obstacles to the treatment of COVID-19. Neutralizing antibodies have achieved good results in the clinical application of the novel coronavirus pneumonia, which can be used for pre-infection protection and treatment of novel coronavirus patients. This review makes a detailed introduction to the mutation characteristics of SARS-CoV-2, focusing on the molecular mechanism of mutation affecting the infectivity of SARS-CoV-2, and the impact of mutation on monoclonal antibody therapy, providing scientific reference for the prevention of SARS-CoV-2 variant strains and the research and development of antibody drugs.